Sistematik Review Penerapan Terapi Komplementer (Massage Effleurage) Untuk Mengurangi Nyeri Persalinan - Annisa' Wigati Rozifa (Jurnal Keperawatan Muhammadiyah, 2021)
Objective:  Labor pain is a natural process, if it is not handled properly it will cause problems such as increased anxiety in the labor process. Several methods are offered to reduce pain in labor, both pharmacological and non-pharmacological methods. One of the non-pharmacological methods that are effective in reducing pain is effleurage massage. The purpose of this literature study is to examine and compare the results of previous studies that discuss the effect of complementary effleurage massage therapy on the intensity of labor pain.. Methods:  The research method used is a systematic review. Sources of research were obtained from literature via the internet in the form of research results obtained about effective massage on labor pain. The search was conducted using the Google Scholar database using the keywords: “massage, effleurage, labor”. Filtering and selecting articles using PRISMA Flowchart. The third keyword search results yielded 445 articles. Then the articles were carried out with the criteria for the year of publication, they obtained 177 articles. Furthermore, it was carried out based on the article on the topic and type of research obtained by 22 articles. Articles The subsequent selection of articles for completeness and the elimination of duplicate articles resulted in 10 articles.Results:  The ten articles mostly discuss the impact of complementary therapies, especially effleurage massage, which can reduce pain during labor. Seven articles carried out effleurage massage intervention in the first stage of the active phase. There are two studies that were carried out in the first stage of the latent phase of labor. One other article mentions that it was carried out in the first stage, not clearly stated the active phase, the latent phase, or bothConclusion:  Conclusions based on this study indicate that the use of effleurage massage in reducing pain in the first stage of labor